THE RELATIONSHIP AMONG REPEATED SPRINT AND CHANGE OF DIRECTION ABILITIES IN FOOTBALL PLAYERS WITH CEREBRAL PALSY (Kinesiology, 2020)
This study aimed to describe and determine relationships between repeated sprint and change of direction abilities in football players with cerebral palsy according to four sport classes (FT5 to FT8). Seventeen male football players with cerebral palsy took part in this study (23.0±4.7 years, 65.9±9.5 kg, 168.8±5.9 cm). The repeated sprint ability (6×40-m sprints with a 20-second recovery) was evaluated to determine the best sprint time, mean sprint time, and percentage of sprint decrement. The difference in lactate concentration was determined using blood samples taken three minutes before and after testing. The Illinois Agility Test (IAT) was also used to assess players’ change of direction ability. The FT8 players had better performance (p